Samuel Davis Sturgis papers - Sturgis, Samuel Davis, 1822-1889.
Typewritten transcripts of three letters (1851-1866) from Sturgis to family members relating to personal matters, Indian wars, politics, and military affairs and of a note written by his wife, Jerusha Wilcox Sturgis; ALS (1881 May 14) from author John G. Nicolay to Gen. Irvin McDowell regarding a proposed history of Civil War campaigns; and handwritten transcript of a newspaper article on Sturgis.
In part, handwritten and typewritten transcripts.
Army officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: McDowell, Irvin, -- 1818-1885 -- Correspondence; Nicolay, John G. -- 1832-1901 -- Correspondence; Sturgis, Jerusha Wilcox -- Correspondence; United States. -- Army -- History -- 19th century; Indians of North America -- Government relations; Indians of North America -- Wars -- 1815-1875.; United States -- History -- Civil War, 1861-1865 -- Campaigns; Army officers